Dapagliflozin inhibits ferroptosis to improve chronic heart failure by regulating Nrf2/HO-1/GPX4 signaling pathway - Jing Zhang; Xuefeng Chen; Shilin Lv; Qingqing Hao (PLoS ONE, 2025)
Objective To study the effect of Dapagliflozin on ferroptosis in rabbits with chronic heart failure and to reveal its possible mechanism. Methods Nine healthy adult male New Zealand white rabbits were randomly divided into Sham group (only thorax opening was performed in Sham group, no ascending aorta circumferential ligation was performed), Heart failure group (HF group, ascending aorta circumferential ligation was performed in HF group to establish the animal model of heart failure), and Dapagliflozin group (DAPA group, after the rabbit chronic heart failure model was successfully made in DAPA group). Dapagliflozin was given by force-feeding method. Echocardiography was used to assess cardiac function, HE staining to evaluate pathological changes in the heart, Prussia blue staining to observe iron ions in myocardial tissue, and enzyme-linked immunosorbent assay (ELISA) to determine serum levels of the inflammatory factors interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) at the end of week 12 and/or the end of week 16. The oxidative stress related indexes of malondialdehyde (MDA), superoxide dismutase (SOD) and superoxide dismutase (GSH-Px) in serum were quantitatively analyzed by colorimetry. Protein expression levels of nuclear factor E2-related factor 2(Nrf2), heme oxygenase-1(HO-1), glutathione peroxidase 4(Gpx4) were detected by Western blot. Results In animals with chronic heart failure, Dapagliflozin improved cardiomyocyte hypertrophy, degeneration and necrosis. Dapagliflozin increased serum GSH-Px and SOD levels and decreased IL-1β, IL-6, TNF-α and MDA levels (P < 0.05) in a rabbit model of heart failure. Dapagliflozin also decreased cardiac iron ion levels and increased Nrf2, HO-1 and GPX4 protein expression. Conclusion Dapagliflozin can improve heart failure by inhibiting oxidative stress and ferroptosis, and its mechanism may be related to the regulation of Nrf2/HO-1/GPX4 signaling pathway.